Students’ Coherence Development in Learning English a Case Study in Writing Class at English Department Year 2009-2008 in FKIP UHN Pematang Siantar - Reina Adelina Sipahutar; Bertaria Sohnata Hutauruk (Bandar Lampung University (UBL), 2013)
This paper deals with the Students’ Coherence Development in learning English Language: A case study in Writing Class at English Department Year 2009-2008 in FKIP UHN Pematangsiantar. The writers have the basic assumptions that the students have problems in developing of topic sentence into a reasonable number of supporting sentences such as cohesion, coherence, and unity of the paragraph All the data are analyzed based on the writing with its definition, recount paragraph, types of paragraph, topic sentence, supporting sentence and conclusion. It relates to the theory of Alexander (1965), Harmer (2003), Herman (2009), McCrimon (1963) and Weaver (1975). The subject is the students at English department in FKIP UHN Pematangsiantar year 2009-2009. After analyzing the data, the writer found that After analyzing the data, there are some research findings as the following: (1) there is not well-structured sentence and the supporting sentences are not relevant to prove the topic sentence. (2) topic sentence is not clear because it’s not relevant to the main topic “my campus” that will be elaborated in the paragraph and the word order of the topic sentence is not well-ordered and supporting sentences are not relevant to prove the topic sentence. (3) Some of the supporting sentences are not relevant to support the topic sentence. The students have some mistakes in word choice and structures. For example there should be written “complete facility” instead of fasilities completely. (4) topic sentence is not specific and the topic sentence and the supporting sentences are not correlated. Some of words in the text are misspelled. As the conclusion: first there are lacks in formulating the topic sentences and supporting sentences. Second, the coherence is mostly not well-applied in each data because the supporting sentences are not well-ordered to make the data in logical order.